Chão de passagem: o fazer artístico como errância - Bruno Gonçalves Oliveira Rios (2019)
This dissertation proposes an investigation of possibili- ties for an artistic process developed on the idea of displacement. The gestures of walking and ramble in the streets were taken as procedures that strengthen the elaboration of philosophical, social, urbanistic and aesthetic questions. As an academic project, this research was also made through the accomplishment of art pieces in the studio. The creation of each piece was made connected to the historical investigation of other previous artistic actions and procedures discussed throughout history – starting at the end of the XIX century, passing through the beginning of the XX century and coming up to the presents days – when artists dealt with the act of walking through cities streets. The development of the project as a whole configured a period of intense immersion in the investigation of artistic practices assumed as open and multiple paths, enlarging the borders of conceptual discussion. In addition to the text that composes this volume, a final exhibition was proposed presenting the pieces developed during the project. The pieces in the exhibition are intimately connected to the text’s notes and reverberate then through the arrangement made in the space as another way of making research generously accessible for the public.